2017
DOI: 10.1111/ane.12729
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord atrophy in anterior-posterior direction reflects impairment in multiple sclerosis

Abstract: In patients with MS, atrophy of the upper cervical cord is most evident in the antero-posterior direction. As APW of the cervical cord can be readily derived from standard structural MRI of the brain, APW constitutes a clinically useful neuroimaging marker of disease-related neurodegeneration in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…39 Previous studies in the spinal cord injured population have demonstrated parallel changes in both cord CSA and somatosensory regions 7,40,41 between CSA and hand grip strengths, 18 and between LRW and motor score, 35 whereas APW correlated with sensory scores. 35 In patients with MS, atrophy of the upper cervical cord is evident in APW but not LRW, 42 whereas studies on ALS have only reported on CSA. 3 We did not observe any relationships between motor function and cord metrics in the present large, young, and healthy cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Previous studies in the spinal cord injured population have demonstrated parallel changes in both cord CSA and somatosensory regions 7,40,41 between CSA and hand grip strengths, 18 and between LRW and motor score, 35 whereas APW correlated with sensory scores. 35 In patients with MS, atrophy of the upper cervical cord is evident in APW but not LRW, 42 whereas studies on ALS have only reported on CSA. 3 We did not observe any relationships between motor function and cord metrics in the present large, young, and healthy cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Several large imaging studies in MS have demonstrated extensive cord atrophy. [42][43][44] We also know from longitudinal neuroimaging studies that brain volume decreases with aging and in neurodegenerative disorders such as Alzheimer and Parkinson disease. Whether the CSA of the spinal cord changes over time in healthy individuals is inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…1,[10][11][12] Spinal cord gray matter atrophy has been described at disease onset in patients with clinically isolated syndrome, a harbinger of MS, and is more pronounced in primary progressive compared to relapsing MS patients. [13][14][15][16] Several studies have highlighted the correlation between physical disability and cord and brain atrophy, 10,17,18 and recently a strong relationship between disability and SC gray matter (GM) atrophy has been shown. 12,19 Spinal cord atrophy has also been proposed as a prognostic biomarker for clinical outcomes in patients with traumatic spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has confirmed that SPMS and RRMS patients differ in cervical spinal cord average CSA (p = 0.03) as well as in C7 area (p = 0.002) (125). Atrophy of the upper cervical cord is most evident in the antero-posterior direction, and attains a cranio-caudal pattern with the progression of the disease (126,127). It presents a sensitive biomarker, especially as the estimated annual rate of SCA is greater when compared to the rate of brain atrophy in patients with MS (−1.78 vs. −0.5%) (123,128).…”
Section: Spinal Cord Atrophymentioning
confidence: 79%